Meningkatkan Pemahaman Materi Bioma melalui Ilustrasi 2D: Pendekatan Visual dalam Pembelajaran Geografi - Jeff Minson (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
Biome is one of the materials used in geography. In the biome distribution material, there is a lot of information about the natural conditions, animals, and plants of each biome type. The large amount of information and the delivery of material dominated by text can make it difficult for teenagers to remember or understand the material because they will get bored more quickly when reading text that fills the page, therefore additional instruments are needed to help deliver the material. This study aimed to show the advantages of using 2D illustrations in delivering material and is expected to encourage the creation of more enjoyable but still meaningful learning materials. Through a literature study research approach, researchers collected and analyzed data from journals on visuals with related themes, namely illustration, education, and the distribution of flora and fauna. Through this study, it can be concluded that 2D illustration is one of the media that can attract readers' attention and make readers more comfortable and easy to receive information. In addition to being a complement to information, illustrations can also make it easier for teenagers to remember the shapes of animals, plants, and the natural conditions of a biome. Researchers believe that information from the material on types of biomes can be delivered more effectively and can maintain students' interest in reading with the help of illustrations.